2015
DOI: 10.1039/c5sm01044f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and high-throughput characterization of structural analogues of molecular glassformers: 1,3,5-trisarylbenzenes

Abstract: We report the synthesis and characterization of an analogous series of small organic molecules derived from a well-known glass former, 1,3-bis(1-naphthyl)-5-(2-naphthyl)benzene (α,α,β-TNB). Synthesized molecules include α,α,β-TNB, 3,5-di(naphthalen-1-yl)-1-phenylbenzene (α,α-P), 9-(3,5-di(naphthalen-1-yl)phenyl)anthracene (α,α-A), 9,9'-(5-(naphthalen-2-yl)-1,3-phenylene)dianthracene (β-AA) and 3,3',5,5'-tetra(naphthalen-1-yl)-1,1'-biphenyl (α,α,α,α-TNBP). The design of molecules was based on increasing molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
22
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 59 publications
2
22
1
Order By: Relevance
“…Irregular molecular shapes, non-planarity, the presence of flexible groups, and conformational ambiguity have emerged as structural features that promote glass formation, as opposed to crystallization. [4][5][6][8][9] The design of molecular glasses with improved resistance to crystallization has led to their use in a wide range of practical applications, ranging from photon-ics, [10][11][12] opto-electronics [4][5][6] and nanolithography, [13][14] to formulations for amorphous drugs. [15][16] Although strong and directional intermolecular interactions have long been associated with crystallization and are a well-known tool for engineering crystals, the presence of hydrogen (H) bonds does not necessarily prevent compounds from forming glasses, as evidenced by mexylaminotriazine derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…Irregular molecular shapes, non-planarity, the presence of flexible groups, and conformational ambiguity have emerged as structural features that promote glass formation, as opposed to crystallization. [4][5][6][8][9] The design of molecular glasses with improved resistance to crystallization has led to their use in a wide range of practical applications, ranging from photon-ics, [10][11][12] opto-electronics [4][5][6] and nanolithography, [13][14] to formulations for amorphous drugs. [15][16] Although strong and directional intermolecular interactions have long been associated with crystallization and are a well-known tool for engineering crystals, the presence of hydrogen (H) bonds does not necessarily prevent compounds from forming glasses, as evidenced by mexylaminotriazine derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies discovered that physical vapor deposition (PVD) at substrate temperatures just below T g can yield glasses with properties similar to well-aged glasses in laboratory time scales. Compared to liquid-quenched glasses, these stable glasses have higher density (by ∼ 1.5%) [11,12] and lower heat capacity (by ∼ 4%) [13][14][15]. It has been suggested that surface-mediated equilibration (SME) during PVD provides a route to overcome kinetic barriers for rearrangement, and achieve these low-energy states within hours [16][17][18][19][20][21][22] as opposed to millions of years.…”
mentioning
confidence: 99%
“…In most molecular systems, it is exceedingly challenging to distinguish the role of orientation vs. layering in the observed birefringence. Here, we design a unique molecule, 9-(3,5-di(naphthalen-1-yl)phenyl)anthracene (α, α-A) (inset of Figure 1(b)) [12,35], to decouple these two effects. The anthracyl substituent introduces steric hindrance to resist rotations around the central benzo ring, allowing α, α-A to retain a nearly isotropic shape.…”
mentioning
confidence: 99%
“…4(c) (details in SI). CR-T g measurements were used to extend the dynamical range of the bulk measurements to temperatures below bulk T g [14,29,36]. CR-T g measurements were performed on films with a thickness range of 20 nm< h <100 nm as shown in Fig 4(b) (details in SI S8 and S9).…”
mentioning
confidence: 99%